Cabo Verde Student Assessment : SABER Country Report 2017 - Liberman, Julia; Heinzel Nelson, Jem; Siegel, Tara Danica; Braham, Kamel; Clarke, Marguerite (World Bank, Washington, DC, 2018)
Cabo Verde has focused on increasing student learning outcomes by improving the quality of education in the country. An effective student assessment system is an important component of efforts to improve education quality and learning outcomes because it provides the necessary information to meet stakeholders’ decision-making needs. In order to gain a better understanding of the strengths and weaknesses of its existing assessment system, Cabo Verde decided to benchmark this system using standardized tools developed under the World Bank’s systems approach for better education results (SABER) program. SABER is an evidence-based program to help countries systematically examine and strengthen the performance of different aspects of their education systems. The SABER-student assessment framework is built on the available evidence base for what an effective assessment system looks like. The framework provides guidance on how countries can build more effective student assessment systems. The framework is structured around two main dimensions of assessment systems: the types and purposes of assessment activities and the quality of those activities.